2004
DOI: 10.3347/kjp.2004.42.3.121
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological survey of Giardia spp. and Blastocystis hominis in an Argentinian rural community

Abstract: 2). Statistical analysis revealed that a male sex, flooding of the home, the use of a latrine, and an abdominal pain were correlated with the presence of these parasites, which indicate the importance of these factors in rural communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 12 publications
(15 reference statements)
2
19
0
6
Order By: Relevance
“…The current finding is comparable to previously reported frequencies in several countries including Saudi Arabia (17.5%) [30], Malaysia (25.7%) [31], Jordan (25%) [32], Egypt (31%) [33], 25.78% in Venezuela [34] and 22.9% in Argentina [35]. On the other hand, significantly lower infection rates ranged between 9 and 12% were recently reported in Saudi Arabia [36, 37].…”
Section: Discussionsupporting
confidence: 90%
“…The current finding is comparable to previously reported frequencies in several countries including Saudi Arabia (17.5%) [30], Malaysia (25.7%) [31], Jordan (25%) [32], Egypt (31%) [33], 25.78% in Venezuela [34] and 22.9% in Argentina [35]. On the other hand, significantly lower infection rates ranged between 9 and 12% were recently reported in Saudi Arabia [36, 37].…”
Section: Discussionsupporting
confidence: 90%
“…Vials for a serial coproparasitological analysis and a perianal swab method were delivered to the parents of each of the children taking part in this study [30,31]. Instructions for sample taking were imparted orally and in writing to parents/guardians.…”
Section: Methodsmentioning
confidence: 99%
“…In Latin America almost 15% of the rural population is infected with Giardia [Atías, 1999]. In Argentina, two human studies showed a prevalence of 10% in urban areas, 34% in small towns (same as villages considered in our study) [Gamboa et al, 2003], and 4% in rural areas [Minvielle et al, 2004]. In animals from this region the reported prevalence of Giardia is 7.5% in cattle, 18.6% in dogs, and 3.9% in rodents ].…”
Section: Introductionmentioning
confidence: 94%